CircRNA circ_0005273 contributes to the cisplatin resistance of cervical cancer cells by sponging miR-133b. (3rd October 2022) - Wu, Lixia; Gao, Jing; Liu, Subin; Jia, Yuling; Li, Cairan; Duan, Lihong
Abstract: Circular RNAs (circRNAs) have been found to play important roles in drug resistance of human neoplasms. The aim of this study was to explore the effect of circ_0005273 on cisplatin (DDP) resistance of cervical cancer (CC) cells and identify its underlying mechanism. The quantitative real-time polymerase chain reaction (qRT-PCR) was performed to analyse circ_0005273 and miR-133b expressions, and cell counting kit-8 (CCK-8), Hoechst 33258 staining and caspase-3 activity analysis were performed to evaluate cell proliferation and apoptosis. Luciferase reporter, RNA binding protein immunoprecipitation (RIP) and RNA pull down assays were applied to explore the interaction between circ_0005273 and miR-133b. Our research showed that circ_0005273 and miR-133b expressions were upregulated and downregulated in DDP-resistant CC cancer tissues and cell lines, respectively. Both of circ_0005273 and miR-133b levels were correlated with FIGO stage, DDP status and overall survival rates. Knockdown of circ_0005273 enhanced the sensitivity of DDP-resistant CC cells to DDP by inhibiting cell proliferation and promoting cell apoptosis. Furthermore, circ_0005273 acts as a competing endogenous RNA to modulate miR-133b expression. Downregulation of miR-133b partly reversed the DDP sensitivity of circ_0005273 knockdown in DDP-resistant CC cells. In summary, our study elucidated the role of circ_0005273/miR-133b axis in DDP resistance of CC cells, which might be a potential therapeutic target for DDP-resistant CC patients. Impact Statement: What is already known on this subject? The detailed regulatory mechanisms underlying DDP chemoresistance are still unclear. Recently, literatures reported that circ_0005273 exerts a regulatory role in the tumorigenesis and progression of human cancers including thyroid carcinoma, pancreatic carcinoma, colorectal carcinoma and breast carcinoma. What do the results of this study add? Circ_0005273 contributes to the DDP resistance of CC cells via sponging miR-133b. What are the implications of these findings for clinical practice and/or further research? The results help to reverse DDP chemoresistance, and the circ_0005273/miR-133b axis might be a potential therapeutic target for DDP-resistant CC patients.